Evaluating the Potential of Container-Based Sanitation : x-runner in Lima, Peru - World Bank (World Bank, Washington, DC, 2019)
This case study examines the container-based sanitation (CBS) service provided by x-runner in the low-income formal/informal settlements in peri-urban Lima. x-runner provides a safe sanitation chain in poor nonsewered neighborhoods in the hills of the outskirts of southwest Lima for a population that does not have (and probably will not have for some years) any safe or hygienic alternative. x-runner operates in difficult-to-access areas, sometimes relying on lockers for users to drop off their sealed full containers. The company is leveraging the capacities of its suppliers to reduce the complexity of its business to a manageable level and the number of customers has been growing steadily, with an average of around 24 new households per month. Although some customers expressed the view that the price for the service is high, they appear to be willing to pay it and the level of satisfaction with the service for x-runner customers is high. Going forward, an explicit recognition of CBS—or a category into which CBS clearly falls—as a viable sanitation system for the urban poor, would be an important factor for enabling public sector support.